Titanium dioxide/agglomerated-free reduced graphene oxide hybrid photoanode film for dye-sensitized solar cells photovoltaic performance improvement - Abu Bakar Suriani (2020)
In this work, the role of agglomerated-free reduced graphene oxide (rGO) in the modification of titanium dioxide (TiO2) photoanode film was investigated for the enhancement of photovoltaic performance in dye-sensitized solar cells (DSSCs). The rutile TiO 2 nanorods–nanoflowers (NRs–NFs) and the photoanode layer consisting of anatase TiO 2 nanoparticles (NPs) were synthesized by the simple hydrothermal growth and squeegee method, respectively. Post-annealing treatment of TiO 2 NRs–NFs was also done in order to investigate its effect on the DSSCs performance. Meanwhile, the rGO solution was produced by reducing a graphene oxide (GO) solution utilizing hydrazine hydrate via a chemical reduction process. The initial GO solution was synthesized by electrochemical exfoliation assisted by a hyper-branched sodium 1,4-bis (neopentyloxy)-3-(neopentyloxycarbonyl)-1,4-dioxobutane-2-sulphonate (TC14) surfactant. The produced TC14-rGO was also hybridized with multi-walled carbon nanotubes (MWCNTs), which then coated by thin platinum (Pt) NPs (TC14-rGO_MWCNTs/Pt) and used as counter electrode (CE) thin film. Based on solar simulator measurements, the highest energy conversion efficiency (η) (1.559%) was achieved by TiO 2 NRs–NFs/TC14-rGO/TiO 2 NPs hybrid photoanode film with the short current density (J sc ), open circuit voltage (V oc ), and fill factor (FF) of 3.275 mA/cm 2 , 0.747 V, and 53.5, respectively as compared to others fabricated photoanode films; non-ann TiO 2 NRs–NFs/TiO 2 NPs (1.215%), ann TiO 2 NRs–NFs/TiO 2 NPs (1.462%), and TiO 2 NRs–NFs/TiO 2 NPs/TC14-rGO (0.525%). This result shows that the utilization of TC14-rGO for both photoanode and CE film increases the conductivity of the film. High η was also supported by high dye adsorption promoted by TiO 2 NPs as the top photoanode layer.